Lidocaine spray compared with submucosal injection for reducing pain during loop electrosurgical excision procedure: A randomized controlled trial - Asama Vanichtantikul (2018)
OBJECTIVE:: To examine the effectiveness of lidocaine spray compared with conventional lidocaine submucosal injection during a loop electrosurgical excision procedure (LEEP). METHODS:: Women undergoing LEEP for any degrees of cervical intraepithelial neoplasia were invited to participate. The participants were randomly assigned into two groups. In group 1 (injection), the participants were anesthetized with 1.8 mL (36 mg) of 2% lidocaine with 1:100,000 epinephrine injected submucosally using a pressure syringe injector with a 27-gauge needle tip at 3, 6, 9, and 12 o'clock locations of the ectocervix. For group 2 (spray), the patients were locally anesthetized with four puffs (40 mg) of 10% lidocaine spray applied thoroughly to the ectocervix. The patients rated their pain according to a 10-cm visual analog scale at different points during the procedure including baseline, postanesthesia, excision, and 30 minutes postexcision. Primary outcomes were the excision pain score and its difference from the baseline. RESULTS:: One hundred one patients (51 in the injection group and 50 in the spray group) participated in the study. The baseline pain scores, the excision pain scores, the difference between the excision and the baseline pain scores, and the postexcision pain scores were comparable between the study groups. The median postanesthesia pain score and the median difference of the postanesthesia score from baseline were significantly higher in the injection group, 3.4 compared with 0.6 and 1.9 compared with 0.0, respectively (P < .01). CONCLUSION:: Lidocaine spray is an effective and practical alternative measure for reducing pain associated with electrical excision of the cervix during LEEP. © 2013 by The American College of Obstetricians and Gynecologists. Published by Lippincott Williams & Wilkins.